2015
DOI: 10.1002/adfm.201500287
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Patterning of Different Cells Via Optical Assembly of 1D Periodic Cell Structures

Abstract: Flexible patterning of different cells into designated locations with direct cell–cell contact at single‐cell patterning precision and control is of great importance, however challenging, for cell patterning. Here, an optical assembly method for patterning of different types of cells via direct cell–cell contact at single‐cell patterning precision and control is demonstrated. Using Escherichia coli and Chlorella cells as examples, different cells are flexibly patterned into 1D periodic cell structures (PCSs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 24 publications
(39 reference statements)
0
24
0
Order By: Relevance
“…25 However, this process requires several days to form aggregates. 26 Above all, microuidic platforms offer rapid manipulation of cells for aggregation and patterning using passive microwell arrays, 10,11,23 or active methods such as magnetic, 27 optical, 28 and electrical 14,26,29 techniques. 10,26 This requires additional fabrication steps for selective patterning of adhesion treated sites, such as using a mask to selectively add collagen bers.…”
Section: Introductionmentioning
confidence: 99%
“…25 However, this process requires several days to form aggregates. 26 Above all, microuidic platforms offer rapid manipulation of cells for aggregation and patterning using passive microwell arrays, 10,11,23 or active methods such as magnetic, 27 optical, 28 and electrical 14,26,29 techniques. 10,26 This requires additional fabrication steps for selective patterning of adhesion treated sites, such as using a mask to selectively add collagen bers.…”
Section: Introductionmentioning
confidence: 99%
“…One main concern about this optical strategy for single‐bacterium labeling and analysis is photodamage to the trapped bacteria by the laser beam. Fortunately, we have previously shown that the cell viability was not affected by the trapping laser at an even larger optical power of ≈30 mW, with other conditions similar; in fact, even cell growth and division can be directly observed after trapping . Therefore, photodamage induced by the laser beam with an optical power less than 30 mW can be ignored for single‐bacterium labeling and sizing using our method.…”
Section: Resultsmentioning
confidence: 69%
“…Figure 5b shows the output light field distribution of a typical tapered fiber. It can be seen that the light is concentrated at the front end of fiber so that the cells can be trapped on the axis of the front end of the fiber and arranged into an ordered structure, as shown in Figure 5c [17].…”
Section: Basic Principlesmentioning
confidence: 99%
“…(b) Simulation of electric field intensity distribution of the fiber-based optical tweezers. (c) A chain of yeast cells was trapped by the fiber-based optical tweezers[17].…”
mentioning
confidence: 99%